Manganese (Mn) removal by adsorption using Palm Oil Fuel Ash (POFA) - Mohd Mokhtar, Mohamad Akmal (Universiti Teknologi Petronas, 2011)
Several studies have been conducted on the potential of POFA as an adsorbent to remove heavy metals such as lead and zinc. However, there is limited literature on the removal of manganese using POF A. The main objective of this research is to use POFA to adsorb manganese in aqueous solution. This study focuses on manganese removal by adsorption using POF A without pre-treatment or activation and varying the operating parameters related to adsorption process such as the amount of adsorbent, agitation time, and initial metal concentration. The results show that POF A is a good adsorbent for manganese removal with removal of manganese over 98%. The optimum contact time, adsorbent dosage and initial manganese concentration is 15 minutes, 0.5g, and lOppm respectively. Characterization ofPOFA was done before the adsorption where the BET surface area is 10.72 m2/g, the particle size is 21.125flm and the carbon content is 52.26%. FTIR analysis showed the hydroxyl, carboy!, alcohol, ethers and esters. The adsorption process followed the Freundlich isotherm with R2 = 0.9668 and Pseudo Second Order with R2= 0.9999.